Eco-preneurship education and its role in developing sustainability and entrepreneurship competences and eco-preneurial intentions - Christou, Antonia; Yiatros, Stylianos; Ioannou, Andri (My University, 2026)
This study examines how an eco-preneurship course integrated into an engineering curriculum supports the development of entrepreneurship and sustainability competences, as well as the formation of eco-preneurial intentions. Informed by the EntreComp and GreenComp frameworks and the Theory of Planned Behavior, the research investigates how students engage with sustainability challenges through experiential entrepreneurial learning. Data were collected from pitchdeck assessments and semi-structured interviews with eleven participants. Findings indicate that the course fostered the development of a wide range of competences, boosting their confidence in entrepreneurial skills and deepening their understanding of engineering's environmental impact. Although the strength of entrepreneurial intentions varied, many participants experienced a mindset shift, increasingly aligning sustainability with their personal and professional goals. Some began to see eco-preneurship as a viable path, while others emphasized the broader applicability of the competences acquired for their future professional roles in engineering and other fields shaped by technological and sustainability transformations. The study underscores the value of interdisciplinary education in building human capital and mindset transformation and offers exploratory insights on applying the Theory of Planned Behavior in an eco-preneurship context within engineering education.
Keywords: Eco-preneurship education; Entrepreneurship education; GreenComp; EntreComp; Theory of planned behavior; Environmental sustainability